Defining Neonatal Serious Illness: Perspectives of Nurses and Social Workers - Guttmann, Katherine F; Raviv, Gabriella N; Fortney, Christine A; Weintraub, Andrea S (Journal of palliative medicine, 2023)
To explore (1) how neonatal nurses (NN) and social workers (SW) define serious illness and (2) how physician, nurse, and SW perceptions of serious illness differ. Prospective survey study. Members of the National Association of Neonatal Nurses or the National Association of Perinatal Social Workers. We circulated a modified version of a previously developed survey. Participants were given a list of definition components and asked to rank components by importance and to suggest modifications. Eighty-eight percent of participants agreed with our definition of neonatal serious illness. NN and SW differ in important ways in their views of neonatal serious illness when compared with physicians and parents. Our definition of neonatal serious illness has broad acceptability and may be useful for clinical care and research. Future work should prospectively identify patients with neonatal serious illness and establish the usefulness of our definition in real time.